1995
DOI: 10.1177/002224379503200204
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Culture and Socioeconomics on the Performance of Global Brand Image Strategies

Abstract: Developing and managing brand image is an important part of a firm's marketing program. However, little research has been done (1) on linking the use of brand image strategies to product performance or (2) on managing brand images in global markets. The author examines the brand image-performance linkage for consumer goods in two categories marketed internationally. He also develops a conceptual framework that identifies various cultural and socioeconomic environmental characteristics of foreign markets that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
272
0
8

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(301 citation statements)
references
References 41 publications
11
272
0
8
Order By: Relevance
“…Conversely, a cultural context that supports altruistic and ecological awareness champions entrepreneurs who pursue social and environmental value creation targets. Culture can also affect consumers' needs (Roth 1995), thus impacting how founders aim to satisfy such needs. We contend that culture, understood in terms of post-materialism, influences the compositions of blended value creation goals.…”
Section: Ethics Of Care Ethics Of Justice and Blended Value Creatiomentioning
confidence: 99%
“…Conversely, a cultural context that supports altruistic and ecological awareness champions entrepreneurs who pursue social and environmental value creation targets. Culture can also affect consumers' needs (Roth 1995), thus impacting how founders aim to satisfy such needs. We contend that culture, understood in terms of post-materialism, influences the compositions of blended value creation goals.…”
Section: Ethics Of Care Ethics Of Justice and Blended Value Creatiomentioning
confidence: 99%
“…Although Hofstede includes four dimensions of cultural values in his original presentation, two have proven more salient in a variety of subsequent empirical studies (e.g., Graham et al, 1994;Roth, 1995) -individualism/collectivism and power distance. ''Individualism pertains to societies in which the ties between individuals are loose: everyone is expected to look after himself or herself and his or her immediate family'' (Hofstede, 1991, p. 51).…”
Section: Cultural Valuesmentioning
confidence: 99%
“…The construct of modernity also recognizes that although cultures tend to transcend entire nations, social and economic conditions often vary markedly within countries (Roth, 1995). Thus, substantial differences in income, mobility, media access, employment, and other socioeconomic characteristics may yield significant intranational variations.…”
Section: Theorymentioning
confidence: 99%
“…Just as more modern individuals have been found to embrace institutions and cultural events that have recently evolved (Inkeles, 1983), so too more modern consumers would engage in recently evolved consumption activities. Roth (1995) found that the extent to which consumers are exposed to Western, materialoriented consumption cultures influenced their attraction to specific products. For Asian consumers, recently evolved activities tend to be Western in origin as markets in the region open themselves to the rest of the world.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation